2020
DOI: 10.1038/s41598-020-72002-w
|View full text |Cite
|
Sign up to set email alerts
|

Activity-based protein profiling of rice (Oryza sativa L.) bran serine hydrolases

Abstract: Rice bran is an underutilized agricultural by-product with economic importance. The unique phytochemicals and fatty acid compositions of bran have been targeted for nutraceutical development. The endogenous lipases and hydrolases are responsible for the rapid deterioration of rice bran. Hence, we attempted to provide the first comprehensive profiling of active serine hydrolases (SHs) present in rice bran proteome by activity-based protein profiling (ABPP) strategy. The active site-directed fluorophosphonate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Because serine hydrolases all use a highly nucleophilic active site serine, it is possible to use reactive electrophiles such as fluorophosphonates (FPs) to develop activity-based probes (ABPs) to label and track their activity in live cells and even whole organisms . FP-based probes enable global profiling of serine hydrolases across various organisms by a method known as activity-based protein profiling (ABPP). Using the broadly reactive fluorphosphonate probe, FP tetramethylrhodamine (FP-TMR), we recently identified a family of metabolic serine hydrolases in S. aureus that we named fluorophosphonate-binding hydrolases (Fphs; FphA–J) .…”
Section: Introductionmentioning
confidence: 99%
“…Because serine hydrolases all use a highly nucleophilic active site serine, it is possible to use reactive electrophiles such as fluorophosphonates (FPs) to develop activity-based probes (ABPs) to label and track their activity in live cells and even whole organisms . FP-based probes enable global profiling of serine hydrolases across various organisms by a method known as activity-based protein profiling (ABPP). Using the broadly reactive fluorphosphonate probe, FP tetramethylrhodamine (FP-TMR), we recently identified a family of metabolic serine hydrolases in S. aureus that we named fluorophosphonate-binding hydrolases (Fphs; FphA–J) .…”
Section: Introductionmentioning
confidence: 99%
“…13 FP-based probes enable global profiling of serine hydrolases across various organisms by a method known as activity-based protein profiling (ABPP). [18][19][20][21][22][23][24][25] Using the broadly reactive fluorphosphonate probe, FP tetramethylrhodamine (FP-TMR), we recently identified a family of metabolic serine hydrolases in S. aureus that we named fluorophosphonate-binding hydrolases (Fphs; FphA-J). 26 Among the Fphs, we found that the lipid esterase FphB is likely a virulence factor important for infection in the heart and liver in vivo.…”
Section: Introductionmentioning
confidence: 99%